2018
DOI: 10.1080/03639045.2018.1438459
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles for the oral delivery of tenofovir disoproxil fumarate: formulation optimization, characterization and ex vivo and in vivo evaluation for uptake mechanism in rats

Abstract: These results show the ability of the designed chitosan based nanoparticles in enhancing the oral absorption of TDF along the oral route by utilizing the active endocytic uptake pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Ulu et al aimed to develop TAF loaded in simple chitosan nanoparticles and found an EE of approximately 50% [ 29 ]. In another study, Shailender et al found an EE of 48.2%, but they prepared nanoparticles of chitosan loaded with a drug that was similar to that used in the current project [ 35 ]. The literature reported the effect of the molecular weight of the polymer and found that the EE and molecular weight have a direct relation with each other [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulu et al aimed to develop TAF loaded in simple chitosan nanoparticles and found an EE of approximately 50% [ 29 ]. In another study, Shailender et al found an EE of 48.2%, but they prepared nanoparticles of chitosan loaded with a drug that was similar to that used in the current project [ 35 ]. The literature reported the effect of the molecular weight of the polymer and found that the EE and molecular weight have a direct relation with each other [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results were similar to the study reported by Ulu et al, where a higher zeta potential of 42.8 mV was observed for chitosan due to its cationic nature [ 29 , 41 ]. In other studies, Yien et al [ 42 ] and Shailender et al [ 35 ] prepared drug-loaded chitosan nanoparticles and reported higher zeta potential values. Similar results were reported by Machado et al, where they fabricated composites of nanoparticles (tenofovir-loaded poly(lactic-co-glycolic acid)/stearylamine) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, different nanoparticles (NPs) have been successfully synthesized to load TDF. Chitosan-based nanoparticles coupled with TDF was prepared, characterized and used for optimal oral absorption in experimental rats 27 . Also, Pokharkar and Co-workers fabricated polymer-lipid nanocarrier to deliver TDF intranasally 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The optimized freeze dried ECONPs were kept in sealed glass vials (n=3) and were stored at 25±2°C with a relative humidity (RH) of 60±5% for 3 months in stability chamber (Remi, Mumbai, India). Samples were collected at a monthly interval and evaluated for morphology, zeta potential, FTIR, drug content, and DR [29].…”
Section: Stability Studiesmentioning
confidence: 99%